2003
DOI: 10.1096/fj.02-0811com
|View full text |Cite
|
Sign up to set email alerts
|

Folding of HIV‐1 Envelope glycoprotein involves extensive isomerization of disulfide bonds and conformation‐dependent leader peptide cleavage

Abstract: Human immunodeficiency virus binds and enters cells via the Envelope glycoprotein gp160 at its surface. In infected cells, gp160 is found not only on the plasma membrane but also in the endoplasmic reticulum (ER). Our aim was to establish rate-determining steps in the maturation process of gp160, using a radioactive pulse-chase approach. We found that gp160 has an intricate folding process: disulfide bonds start to form during synthesis but undergo extensive isomerization until the correct native conformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
139
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(149 citation statements)
references
References 55 publications
(61 reference statements)
8
139
2
Order By: Relevance
“…Devising an appropriate purification strategy may require a better understanding of the nature of nonfunctional Env. Our recent observations indicate that, contrary to popular perceptions, nonfunctional Env is not derived from trimer dissociation (19,20,36,69) but instead is a mostly static species that is coexpressed on particles alongside the trimer during synthesis. Nonfunctional…”
contrasting
confidence: 62%
“…Devising an appropriate purification strategy may require a better understanding of the nature of nonfunctional Env. Our recent observations indicate that, contrary to popular perceptions, nonfunctional Env is not derived from trimer dissociation (19,20,36,69) but instead is a mostly static species that is coexpressed on particles alongside the trimer during synthesis. Nonfunctional…”
contrasting
confidence: 62%
“…In light of the current interests regarding how different soluble (42), polytopic (50,51), or multisubunit (48,52) proteins fold in the ER, our work on DM demonstrates that two subunits of a heterodimeric complex can direct each others oxidative folding. We have shown that DM␤ chains require DM␣ chains to prevent misoxidation and conversely, DM␣ chains need DM␤ with the right disulfide bonds for proper oxidation of the DM complex.…”
Section: Discussionmentioning
confidence: 98%
“…However, signal sequence cleavage for some proteins can also be a posttranslational event. For instance, the HIV envelope glycoprotein signal sequence is cleaved posttranslationally after the protein has folded to some degree (Li et al 1996;Land et al 2003). Tethering the amino-terminus to the membrane during the initial stages of folding appears to help direct the early folding and maturation processes; and because of this the timing of cleavage can be important.…”
Section: Signal Sequence Cleavagementioning
confidence: 99%